Model Ekonomi Sirkular Berbasis Limbah Pertanian Melalui Produksi Media Tanam Organik di Desa Sintung - Nila Rahayu; Nadia Nuril Ferdaus; Adrianda Anwar; I Gusti Agung Arista Pradnyani; Sri Maryanti (Universitas Mataram, 2026)
This community service program aims to strengthen the local economy through the application of a circular economy approach by utilizing agricultural and livestock waste as organic growing media. The program was conducted in Sintung Village, Pringgarata District, Central Lombok Regency, West Nusa Tenggara, where agricultural activities generate abundant waste such as cow manure and rice husks that remain underutilized. A participatory-descriptive approach was employed to actively engage farmers, livestock breeders, and local communities throughout the implementation process. The activities included problem identification, socialization of circular economy concepts, hands-on training in producing organic growing media, and continuous assistance to ensure community independence. Data were collected through observation, short interviews, and documentation, and analyzed descriptively to evaluate community participation, knowledge improvement, and potential economic benefits. The results indicate increased community awareness of waste utilization, the successful production of functional organic growing media, and potential reductions in agricultural production costs. Furthermore, the program demonstrates opportunities for developing waste-based products as alternative sources of household income. This community service contributes to sustainable rural economic development by integrating environmental management and economic empowerment at the village level.